Extensive Subcutaneous Emphysema and Pneumomediastinum after Ecstasy Ingestion. (24th September 2013) - Gungadeen, A.; Moor, J.
Abstract : Objective . To present a rare case of extensive subcutaneous emphysema and spontaneous pneumomediastinum following ingestion of Ecstasy in a young adult. We also review the relevant literature and discuss how this case supplements it. Case Report . We report a case of a 19-year-old man with a history of painless neck and chest swelling, and no chest pain or breathlessness, after consuming Ecstasy tablets. Radiological imaging showed evidence of pneumomediastinum and extensive subcutaneous emphysema. The patient remained well under observation and his symptoms improved with conservative management. Conclusions . Subcutaneous emphysema and pneumomediastinum after Ecstasy ingestion is uncommon. Cases are often referred to the otolaryngologist as they can present with neck and throat symptoms. Our case showed that the severity of symptoms may not correlate with severity of the anatomical abnormality and that pneumomediastinum should be suspected in Ecstasy users who present with neck swelling despite the absence of chest symptoms. Although all cases reported so far resolved with conservative management, it is important to perform simple investigations to exclude coexisting serious pathology.